Perbaikan Nilai Nutrisi Jerami Padi Melalui Suplementasi Tepung Daun Lamtoro pada Sapi Peranakan Ongole Jantan - S D Widyawati (Universitas Sebelas Maret (UNS), 2010)
Since rice straw is seasonal and low quality roughage, a supplementation for it is needed. Lamtoro leave meal (LLM), having both soluble and by-pass protein so, its enough potential to supply nutrients for optimize of rumen microbes and improving animal performance. When fed to animals with high portion of roughage can affect methane production highly, an adding reduction methane agent for it is needed, like ketepeng leave meal (KLM) and lemuru fish oil (LFO). Supplementation with LLM significantly increased dry matter and crude fiber intake (p<0.05). This fact showed that LLM supplementation optimized rumen fermentation by microbes. Comparisonbetween LLM-KLM and LLM-LFO to basal diet clearly showed that basal diet is the lowest (p<0.01) performance (0.19 vs 0.21; 0.23kg/h/d), however, the animal fed basal diet degraded crude fiber was significant (p<0.05) higher (74.49 vs 69.02; 65.17%). It is apparent from this experiment that supllementation with lamtoro leave meal by adding both ketepeng leave meal and lemuru fish oil as a reduction methane agent are palatable, fermentable and reasonably digestible. It is recommended to use rice straw as a supplement.Key words : Lamtoro, digestibility, performance, PO beef cattle, ketepeng and lemuru fish oil